Activation of Wnt/β-catenin signaling in Muller glia protects photoreceptors in a mouse model of inherited retinal degeneration. (April 2015) - Patel, Amit K.; Surapaneni, Krishna; Yi, Hyun; Nakamura, Rei E.I.; Karli, Sapir Z.; Syeda, Sarah; Lee, Tinthu; Hackam, Abigail S.
Abstract: The canonical Wnt/β-catenin ("Wnt") pathway is an essential signaling cascade in the embryonic central nervous system (CNS) that regulates neuronal differentiation and survival. Loss of Wnt signaling in developing and adult tissue has been implicated in numerous CNS diseases, but the precise role of Wnt in regulating neuronal survival, and how its absence could lead to disease, is not understood. In this study, we investigated the effect of Wnt activation on neuronal survival in the adult retina, and identified cellular and molecular mediators. Pan-retinal Wnt signaling activation using Wnt3a induced functional and morphological rescue of photoreceptor neurons in the rd10 mouse model of retinal degeneration. Furthermore, Wnt activation using constitutively active β-catenin specifically targeted to Muller glia increased photoreceptor survival and reduced markers of glial and neuronal remodeling. Wnt-induced photoreceptor protection was associated with elevated levels of the prosurvival protein Stat3, and was reduced by shRNA-mediated knock-down of Stat3, indicating cross-talk between survival pathways. Therefore, these data increase our understanding of the role of Wnt signaling in the retina, and identify radial Muller glia as important cellular mediators of Wnt activity. Highlights: The study tested the role of Wnt/β-catenin signaling during retinal degeneration. Wnt signaling protected photoreceptors in the rd10 mouse model. Wnt-induced photoreceptor protection was mediated by Stat3. Radial Muller glia are cellular mediators of protective Wnt signaling.